A novel Ca2+-signal transduction inhibitor, kujigamberol C, isolated from Kuji amber. Issue 9 (2nd September 2019) - Takahashi, Honoka; Koshino, Hiroyuki; Maruyama, Miku; Shinden, Hisao; Kimura, Ken-ichi
ABSTRACT: A novel labdane type diterpenoid, 15-nor-8-labden-13-ol, named kujigamberol C, was isolated from Kuji amber using a modified isolation method to increase the yield of biologically active compounds. The structure was determined using HREIMS, 1D and 2D NMR. Kujigamberol C showed growth-restoring activity against mutant yeast via Ca 2+ -signal transduction. Graphical abstract: : A novel Ca 2+ -signal transduction inhibitor, kujigamberol C, was isolated from Kuji amber. It showed the growth-restoring activity against the mutant yeast.